2017
DOI: 10.1523/jneurosci.3622-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Domain Selectivity in the Parahippocampal Gyrus Is Predicted by the Same Structural Connectivity Patterns in Blind and Sighted Individuals

Abstract: Human ventral occipital temporal cortex contains clusters of neurons that show domain-preferring responses during visual perception.Recent studies have reported that some of these clusters show surprisingly similar domain selectivity in congenitally blind participants performing nonvisual tasks. An important open question is whether these functional similarities are driven by similar innate connections in blind and sighted groups. Here we addressed this question focusing on the parahippocampal gyrus (PHG), a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Due to a large degree of inter-subject anatomical variability, identification of these regions depends critically on within-subject analyses. Here, we demonstrate that, for both sexes, an individual’s unique pattern of resting-state functional connectivity can accurately identify their specific pattern of visual- and auditory-selective working memory and attention task activation in lateral frontal cortex (LFC) using “connectome fingerprinting.” Building on prior techniques (Saygin, Osher et al, 2011; Osher et al, 2016; Tavor et al, 2016; Smittenaar et al, 2017; Wang et al, 2017; Parker Jones et al, 2017), we demonstrate here that connectome fingerprint predictions are far more accurate than group-average predictions and match the accuracy of within-subject task-based functional localization, while requiring less data. These findings are robust across brain parcellations and are improved with penalized regression methods.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Due to a large degree of inter-subject anatomical variability, identification of these regions depends critically on within-subject analyses. Here, we demonstrate that, for both sexes, an individual’s unique pattern of resting-state functional connectivity can accurately identify their specific pattern of visual- and auditory-selective working memory and attention task activation in lateral frontal cortex (LFC) using “connectome fingerprinting.” Building on prior techniques (Saygin, Osher et al, 2011; Osher et al, 2016; Tavor et al, 2016; Smittenaar et al, 2017; Wang et al, 2017; Parker Jones et al, 2017), we demonstrate here that connectome fingerprint predictions are far more accurate than group-average predictions and match the accuracy of within-subject task-based functional localization, while requiring less data. These findings are robust across brain parcellations and are improved with penalized regression methods.…”
mentioning
confidence: 67%
“…Task-based fMRI approaches and other techniques have yielded considerable insights (e.g., Koechlin et al, 2003; Astafiev et al, 2003; Badre, 2008; Fedorenko et al, 2013; Sallet et al, 2013; Nee & D’Esposito, 2016), but many issues remain unresolved. Recent work has demonstrated that an individual’s unique pattern of functional or structural brain connectivity offers an alternative means to localize functional organization in individuals (Saygin, Osher et al, 2011; Osher et al, 2016; Tavor et al, 2016; Smittenaar et al, 2017; Wang et al, 2017; Parker Jones et al, 2017). Findings from our laboratory (Michalka et al, 2015; Tobyne et al, 2017) revealed multiple visual-selective and auditory-selective lateral frontal cortical areas that are nodes of separate whole-brain sensory modality-selective resting-state networks (Figure 1C).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, sounds of big objects or natural scenes preferentially recruit more mesial VOTC regions (Fig. 1B), overlapping with the parahippocampal place area, potentially due to the preserved pattern of structural connectivity of those regions in blind people (Wang et al, 2017). The existence of these innate large-scale brain connections that are specific for each region supporting separate categorical domain may provide the structural scaffolding on which crossmodal inputs capitalizes to reach VOTC in both sighted and blind people, potentially through feed-back connections.…”
Section: Discussionmentioning
confidence: 97%
“…However, using auditory stimuli representing different categories, recent studies have demonstrated a similarity in the functional organization of categoryselective ventral temporal cortex in congenitally blind subjects and sighted controls-arguing that the development of categoryselective map in visual cortex does not rely on visual input and visual experience 8,9 . It has been proposed that the broad organization of ventral visual stream is driven by innate connectivity between regions that process semantic categories 10,11 . Finally, individuals with congenital prosopagnosia show lifelong difficulty in recognizing faces despite normal or almost normal exposure to faces, suggesting that the face recognition deficit in these individuals may have a genetic basis 12 .…”
mentioning
confidence: 99%